Mastering Vmware Vsphere 4. (Sybex Inc, 2011)
A new and updated edition of bestselling Mastering VMware vSphere 4 Written by leading VMware expert, this book covers all the features and capabilities of VMware vSphere. You'll learn how to install, configure, operate, manage, and secure the latest release. Covers all the new features and capabilities of the much-anticipated new release of VMware vSphereDiscusses the planning, installation, operation, and management for the latest releaseReviews migration to the latest vSphere softwareOffers hands-on instruction and clear explanations with real-world examples Mastering VMware vSphere is the.